Individual specialization in the use of space by frugivorous bats - Kerches-Rogeri, Patricia [UNESP]; Niebuhr, Bernardo Brandão [UNESP]; Muylaert, Renata Lara [UNESP]; Mello, Marco Aurelio Ribeiro (Wiley, 2020)
Natural populations are not homogenous systems but sets of individuals that occupy subsets of the species’ niche. This phenomenon is known as individual specialization. Recently, several studies found evidence of individual specialization in animal diets. Diet is a critical dimension of a species’ niche that affects several other dimensions, including space use, which has been poorly studied under the light of individual specialization. In this study, which harnesses the framework of the movement ecology paradigm and uses yellow–shouldered bats Sturnira lilium as a model, we ask how food preferences lead individual bats of the same population to forage mainly in different locations and habitats. Ten individual bats were radiotracked in a heterogeneous Brazilian savanna. First, we modelled intraspecific variation in space use as a network of individual bats and the landscape elements visited by them. Second, we developed two novel metrics, the spatial individual specialization index (SpatIS) and the spatial individual complementary specialization index (SpatICS). Additionally, we tested food-plant availability as a driver of interindividual differences in space use. There was large interindividual variation in space use not explained by sex or weight. Our results point to individual specialization in space use in the studied population of S. lilium, most probably linked to food–plant distribution. Individual specialization affects not only which plant species frugivores consume, but also the way they move in space, ultimately with consequences for seed dispersal and landscape connectivity.
Keywords: Cerrado; Chiroptera; ecology of individuals; interindividual variation; Phyllostomidae; plant–animal interactions; spatial ecology